Exploring Methodological Approaches for Strengthening the Resilience of Coastal Flood Protection System - Igigabel, Marc; Diab, Youssef; Yates, Marissa (Frontiers in Earth Science, 2022)
Coastlines are subject to multiple developments related to land use planning and the effects of climate change. These developments generally lead to an increase in the risk of coastal flooding. This article focuses on systems to protect against this hazard, and presents a bibliographical analysis on methods and operational tools to strengthen their resilience. This analysis is carried out by considering that a system of protection is a component of the territory to which it provides protection and that it is therefore necessary to study in depth the relations between this system and the various components of the territory (the natural environment, the built environment and the social and institutional environment). Based on this hypothesis, the concepts of risk and resilience applied to floods are specified and the protection and adaptation strategies commonly used in recent decades are described. This retrospective on concepts and strategies leads us to structure the state-of-the-art analysis on methods and operational tools in relation to two issues: 1) understanding risks; 2) adapting and transforming protection systems. In each case, the use of the concept of resilience implies a clear distinction between systemic and analytical approaches. Finally, this bibliographical analysis reveals the need to revise the protection system concept in order to promote the integration of these systems in the territories. Accordingly, new methodological developments could be considered using ecosystem and socio-economic approaches.